Identification of the excitation source's circumferential position for rotating blades based on vibration phase. (3rd March 2022) - Niu, Guangyue; Duan, Fajie; Liu, Zhibo; Zhi, Fengyao; Fu, Xiao; Jiang, Jiajia; Guo, Guanghui; Xiong, Bing
Highlights: The blade resonance models under excitation sources are established. A method of identifying excitation sources from blade vibration phase is proposed. An unwrapping method addressing phase ambiguity is proposed. The identification error of excitation source's position is less than ±1°. Abstract: Wake excitation is the main cause of synchronous vibration of large rotating machines' blades, whose circumferential position reflects the distortion position of flow field. However, little research has been published concerning the identification of excitation source's circumferential position based on blade vibration parameters. A new identification method using vibration phase is proposed in this paper. The excitation force model is established along with the forced vibration response model of blades under excitation sources. A phase unwrapping method is proposed to solve phase ambiguity, and the excitation source's circumferential position is achieved through vibration phase and engine orders of the same rotating blade in adjacent resonance regions. Experimental results verified the effectiveness and accuracy of the proposed method. The identification error of excitation source's circumferential position is less than ±1°.